Kebijakan Perimbangan Keuangan antara Pemerintah Pusat dan Daerah Pasca Reformasi - Faisal Akbar Nasution (Fakultas Hukum Universitas Islam Indonesia, 2011)
In the post-reform, the establishment of the Law No. 25 year 1999 about the Financial Proportionality between Central Government and Local Government and the Law No. 33 year 2004 about the Financial Proportionality between Central Government and Local Government, Distribution of Proportionality Resources have turned into the distribution of natural resources of local areas. The issue to be analyzed deals with in what financial sector the local areas initiatively find the revenue sources needed to implement their autonomy as a reflection of a decentralization-based implementation as stated in Constitutional of 1945. The method used in the research is based on the judicial-normative approach by applying the materials of primary law, secondary law, and tertiary law. This research additionally applies a normative-qualitative analysis. The establishment of Regulation on the Financial Proportionality in the post of reform shows a very significant outcome for the implementation of autonomy in the local areas. It is due to the local budget is not merely based on the local revenue but, much more than that, the local areas also have the budget resources originated from the local areas alone – that currently is absorbed by the Central Government.